TUHAN, MANUSIA, DAN BAHASA MENURUT LUDWIG WITTGENSTEIN: SUATU TINJAUAN FILSAFAT AGAMA - Nole, Otniel Aurelius (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Ludwig Wittgenstein was a man with significant contributions. As a philosopher, Wittgenstein had an understanding of how to respond to God's existence. Through his thoughts on language, Wittgenstein stated that human have language and regarded language as a game. Therefore, this research is intended to explain God, man, and language according to Wittgenstein. Library research based on a qualitative method was used in this research and was reviewed with the philosophy of religion. In this research, the writer showed the unique religious life of Wittgenstein. For him, language was part of human life which is used for daily interaction and to carry out religious practices.